Aggregation properties of cold-active lipase produced by a psychrotolerant strain of Pseudomonas palleroniana (GBPI_508). Issue 4 (3rd July 2020) - Jain, Rahul; Pandey, Neha; Pandey, Anita
Abstract: The present study aims to exploit microbial potential from colder region to produce lipase enzyme stable at low temperatures. A newly isolated bacterium GBPI_508 from Himalayan environment, was investigated for the production of cold-active lipase emphasizing on its aggregation properties. Plate based assays followed by quantitative production of enzyme was estimated under different culture conditions. Further characterization of partially purified enzyme was done for molecular weight determination and activity and stability under varying conditions of pH, temperature, and in presence of organic solvents, inhibitors, and metal ions. The psychrotolerant bacterium was identified as Pseudomonas palleroniana following 16S rRNA gene sequencing. Maximum lipase production by GBPI_508 was recorded in 7 days at 25 °C utilizing yeast extract as nitrogen source and olive oil as substrate in the lipase production medium. Triton X-100 (1%) in the medium as emulsifier significantly enhanced the lipase production. Lipase produced by bacterium showed aggregation which was confirmed by dynamic light scattering and native PAGE. SDS-PAGE followed by zymogram analysis of partially purified enzyme showed two active bands of ∼50 kDa and ∼54 kDa. Optimum activity of partially purified enzymatic preparation was recorded at 40 °C while the activity remained nearly consistent from pH 7.0 to 12.0, whereas, maximum stability was recorded at pH values 7.0 and 11.0 at 25 °C. Interestingly, lipase in the partially purified fraction retained 60% enzyme activity at 10 °C. Medium chain p NP ester (C10) was the most preferred substrate for the lipase of GBPI_508. The lipase possessed >50% residual activity when incubated with different organic solvents (25% v/v) except toluene and dichloromethane which inhibited the activity below 50%. Partially purified enzyme was also stable in the presence of metal ions and inhibitors. The study suggests applicability of GBPI_508 lipase in low temperature conditions such as cold-active detergent formulations and cold bioremediation. Graphical Abstract: